A Note on Moment Generating Function of a Linear Combination of Order Statistics from a Bivariate Laplace Distribution - R. Pourmousa; A. Jamalizadeh (Journal of Mathematical Extension, 2013)
. In this note we propose an extended skew-Laplace distribution. We obtain explicit expressions for moment generating function and the two first moments of this distribution. Next, we show that the distribution of a linear combination of order statistics from a bivariate Laplace distribution can be expressed as a mixture of extended skewLaplace distributions. This mixture representation enables us to derive moment generating function and moments of this linear combination